Antibacterial activity of biodentine against Enterococcus faecalis: a systematic review - Subhi, Hasan; Subhi, Nashwah; Alhaidary, Salah; Azeez, Mahmood S.; Tabnjh, Abedelmalek Kalefh (Frontiers in Dental Medicine, 2025)
IntroductionBiodentine is a well-known endodontic material that is applied in various endodontic therapies. Enterococcus faecalis (E. faecalis) is associated with endodontic failure and persistent periapical infection. The purpose of this systematic review was to summarize the available evidence regarding the antibacterial activity of Biodentine against E. faecalis and to compare it to other commercial endodontic materials.MethodsAn electronic search of literature was conducted in PubMed, Scopus, Web of Science, and Google Scholar in addition to a manual search in specialized journals up to May 2024. The eligibility criteria, data extraction, and evaluation of risk of bias were assessed by two independent authors. The risk of bias was evaluated in accordance with Modified CONSORT checklist items for pre-clinical in vitro studies on dental materials.ResultsOut of 343 studies, thirty-seven fulfilled the inclusion criteria and were included in this review. Thirty studies reported a good antibacterial efficacy of Biodentine against E. faecalis. Biodentine was superior to or, at least, as efficacious as MTA, MTA Angelus, GIC, RMGIC, DiaRoot BioAggregate, NeoPutty, iRoot FS, MTA Repair HP, MTA Biorep, Well-Root PT, Activa, NeoMTA 2, Calcimol LC, TotalFill, and IRM. The findings were supported by studies with medium to high risk of bias (low quality).ConclusionsConsidering the limitations of this systematic review, there is accumulating evidence on the antibacterial activity of Biodentine against E. faecalis in context of endodontics. However, randomized clinical trials with well-designed and robust methodologies are required in order to provide information about its clinical behaviour.